Revised Case Finding Protocol for Dysglycemia in Chile: A Call for Action in Other Populations - Nieto-Martinez, Ramfis; Mechanick, Jeffrey I; González-Rivas, Juan P; Ugel, Eunice; Iglesias, Rocío; Clyne, Megan; Grekin, Carlos (Endocrine practice, 2023)
OBJECTIVE: Guidelines recommend case finding for dysglycemia (prediabetes and type 2 diabetes [T2D]) in adults or youth older than 10 years with overweight/obesity, but increased adiposity has not been associated with dysglycemia in some Hispanic populations. This study aims to determine the prevalence of dysglycemia in this population using simplified criteria independent of body mass index and age to request an oral glucose tolerance test (OGTT). METHODS: Cross-sectional retrospective analysis of medical records from a clinical center in Chile (2000-2007). OGTT was obtained from any patient with 1 cardiometabolic risk factor (CMRF) independent of age and body mass index. RESULTS: In total, 4969 adults (mean age ± SD) 45.7 ± 15.9 years and 509 youths 16.6 ± 3.0 years were included. The prevalence (%, 95% CI) of prediabetes doubled that of T2D in youths (14.1%, 1.4-17.4 vs 6.3%, 4.5-8.7) and tripled it in adults (36.0%, 34.7-37.4 vs 10.7%, 9.8-11.5). In underweight and normal-weight adults, 22% (12.0-36.7) and 29.2% (26.4-32.1) had prediabetes, whereas 4.9% (1.3-16.1) and 8.8% (7.2-10.7) had T2D, respectively. In normal weight youths, 10.5% (6.7-15.9) and 2.9% (1.2-6.6) had prediabetes and T2D, respectively. In adults, but not in youths, most dysglycemia categories were related to overweight/obesity. CONCLUSION: This study supports a public health policy to identify more people at risk for cardiovascular disease by implementing a revised case finding protocol for dysglycemia using OGTT in even normal weight patients over 6 years of age when there is at least 1 CMRF. Reanalysis of case finding protocols for cardiometabolic risk in other populations is warranted.
Keywords: obezita; Humans; Overweight; dospělí; nadváha; lidé; Blood Glucose; Diabetes Mellitus, Type 2; Chile; Adult; Retrospective Studies; krevní glukóza; Adolescent; prediabetes; Cross-Sectional Studies; Obesity; retrospektivní studie; diabetes mellitus 2. typu; průřezové studie; Prediabetic State; mladiství